Modern Realism in English-Canadian Fiction - Hill, Colin, 1970- (Book collections on Project MUSE., 2012)
"Much of the scholarship on twentieth-century Canadian literature has argued that English-Canadian fiction was plagued by backwardness and an inability to engage fully with the movement of modernism that was so prevalent in British and American fiction and poetry. Modern Realism in English-Canadian Fiction re-evaluates Canadian literary culture to posit that it has been misunderstood because it is a distinct genre, a regional form of the larger international modernist movement. Examining literary magazines, manifestos, archival documents, and major writers such as Frederick Philip Grove, Morley Callaghan, and Raymond Knister, Colin Hill identifies a 'modern realism' that crosses regions as well as urban and rural divides. A bold reading of the modern-realist aesthetic and an articulate challenge to several enduring and limiting myths about Canadian writing, Modern Realism in English- Canadian Fiction will stimulate important debate in literary circles everywhere."--Publisher's website